Pd-catalyzed one-pot chemoselective hydrogenation protocol for the preparation of carboxamides directly from azides - Bavikar, Sudhir N.; Salunke, Deepak B.; Hazra, Braja G.; Pore, Vandana S.; Thierry, Josiane; Dodd, Robert H. (Tetrahedron Letters, 2010)
Carboxamides were obtained efficiently in high yields from azides on reaction with the corresponding pre-formed activated carboxylic acids in a single-step reductive transformation using hydrogen atmosphere (balloon) under Pd/BaSO(4) or Pd/CaCO(3) catalysis. The method is highly chemoselective and compatible with extremely labile functional groups such as benzyl carbamates, benzyl ethers, benzyl esters, and olefins. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Azide; Carboxamide; Catalytic hydrogenation; Chemoselective; Palladium; Succinimide ester